Penerapan ECS Stemmer untuk Modifikasi Nazief & Adriani Berbahasa Jawa - Nur Hidayatullah; Aji Prasetya Wibawa; Harits Ar Rosyid (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Stemming Javanese affix words using Nazief & Adriani modifications still has problems that cannot be solved such as overstemming, understemming, and unchange. Then there needs to be improvements to improve the performance of Nazief & Adriani modifications. This study aims to improve the performance of Nazief & Adriani modifications using the Enahnced Confix Stripping (ECS) modification method. The results of this study indicate that Enhanced Confix Stripping can improve performance that previously had an accuracy of only 78.2% to 97.9% with an error rate of 2.1%. And fixing errors that originally numbered 98 to 9 errors. But Enhanced Confix Stripping still has problems with the words